2019
DOI: 10.1136/jech-2019-213249
|View full text |Cite
|
Sign up to set email alerts
|

Characterising risk of homicide in a population-based cohort

Abstract: BackgroundHomicide is an extreme expression of violence that has attracted less attention from public health researchers and policy makers interested in prevention. The purpose of this study was to examine the socioeconomic gradient of homicide and to determine whether risk differs by immigration status.MethodsWe conducted a population-based cohort study using linked vital statistics, census and population data sets that included all deaths by homicide from 1992 to 2012 in Ontario, Canada. We calculated age-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The risk of homicide can be influenced by factors that are more prevalent in immigrant communities such as social isolation, cultural attitudes, gender roles, and fewer employment options ( 6 ). In our study, we found a higher risk of homicide among immigrant females, regardless of other characteristics, whereas no differences by citizenship were observed for males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of homicide can be influenced by factors that are more prevalent in immigrant communities such as social isolation, cultural attitudes, gender roles, and fewer employment options ( 6 ). In our study, we found a higher risk of homicide among immigrant females, regardless of other characteristics, whereas no differences by citizenship were observed for males.…”
Section: Discussionmentioning
confidence: 99%
“…It has been frequently highlighted that male gender, young-adult age, low socioeconomic status, and being involved in organized crime are the main risk factors for being victims of homicide ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…To quantify days of care received in the year prior to homicide for MHA and assault, we calculated the proportion of individuals with any health care use and the mean visit length among those with any health care use. We stratified all measures of health care use by sex given that the risk of homicide varies by sex [30,31] and that we had sufficient sample size to examine health care utilisation. We describe the number of individuals who received health care services for both MHA and assault.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the privacy and protection of data, ICES implements a series of physical and logical controls to govern access to information, like the use of secure zones within ICES facilities, complex passwords, and encryption. The use of these data has enabled scientists to answer important policy-relevant questions across different disciplines such as health services research, health economics, epidemiology and public health [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%